Audio Encryption Scheme based on Pseudo-orbit of Chaotic Map - Magalhães, Eduardo; Santos, Thiago; Nepomuceno, Erivelton Geraldo (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2019.10448, 2019)
Chaos-based encryption uses a chaotic dynamic system to encrypt a file. The aim of this study was to investigate the use of the chaotic Cubic Map to encrypt data, in particular, audio files. A simple algorithm was developed to encrypt and decrypt an audio data. The effectiveness of the method was measured by means of the correlation coefficient calculation, spectral entropy and also by comparing waveforms. The measurements were shown to lead to satisfactory confusion levels of the original data, within a few seconds. This indicates that the Cubic Map can be used as a source for encryption keys, with as good or better security indicators when compared to other schemes.